Está en la página 1de 2

7) 𝑿𝒀´ = √𝒀𝟐 − 𝑿𝟐

Despejando:
2
𝑋2𝑌´ + 𝑋2 − 𝑌2 = 0
Comprobando si es homogéneo o no:
𝑓(𝑡𝑋: 𝑡𝑌) = 𝑡 𝑛 𝑓(𝑋: 𝑌)
2
= 𝑡 2𝑋2𝑌´ + 𝑡 2𝑋2 − 𝑡 2𝑌2
2
= 𝑡 2 (𝑋 2 𝑌 ´ + 𝑋 2 − 𝑌 2 ) = 0
Grado 2; es homogéneo.
Integrando, cambio de variable:
Y=UX dy = udx + xdu U´=U´X + U

𝑓(𝑋: 𝑌); 𝑋𝑌 ´ = √𝑌 2 + 𝑋 2
𝑑𝑦
=𝑋 = √𝑌 2 − 𝑋 2
𝑑𝑥
(𝑥𝑑𝑢+𝑢𝑑𝑥)
=𝑋 − 𝑋√𝑈 2 − 1 = 0
𝑑𝑥
𝑋 2 𝑑𝑢+𝑈𝑋𝑑𝑥
= − 𝑋√𝑈 2 − 1
𝑑𝑥

= 𝑋 2 𝑑𝑢 + 𝑈𝑋𝑑𝑥 − 𝑋√𝑈 2 − 1𝑑𝑥

= 𝑋𝑑𝑥(𝑈 − √𝑈 2 − 1) + 𝑋 2 𝑑𝑢
𝑋𝑑𝑥 𝑑𝑢
= + =0
𝑋2 (𝑈−√𝑈 2 −1)

𝑑𝑥 𝑑𝑢
= + =0
𝑋 (𝑈−√𝑈 2 −1)

𝑑𝑥 𝑑𝑢
=∫ +∫ =0
𝑋 (𝑈−√𝑈 2 −1)

= 𝑙𝑛|𝑋| + 𝑘
𝑦(𝑦+√𝑌2 −𝑋2 )
=𝑅: 𝑌 + √𝑌 2 − 𝑋 2 = 𝐶𝑋 3 𝑒 𝑋2